Antimicrobial susceptibility and antibiotic resistance gene transfer analysis of foodborne, clinical, and environmental Listeria spp. isolates including Listeria monocytogenes. Issue 1 (2nd January 2014) - Bertsch, David; Muelli, Mirjam; Weller, Monika; Uruty, Anaïs; Lacroix, Christophe; Meile, Leo
Abstract The aims of this study were to assess antibiotic resistance pheno‐ and genotypes in foodborne, clinical, and environmental Listeria isolates, as well as to elucidate the horizontal gene transfer potential of detected resistance genes. A small fraction of in total 524 Listeria spp. isolates (3.1%) displayed acquired antibiotic resistance mainly to tetracycline (n = 11), but also to clindamycin (n = 4) and trimethoprim (n = 3), which was genotypically confirmed. In two cases, a tetracycline resistance phenotype was observed together with a trimethoprim resistance phenotype, namely in a clinical L. monocytogenes strain and in a foodborne L. innocua isolate. Depending on the applied guidelines, a differing number of isolates (n = 2 or n = 20) showed values for ampicillin that are on the edge between intermediate susceptibility and resistance. Transferability of the antibiotic resistance genes from the Listeria donors, elucidated in vitro by filter matings, was demonstrated for genes located on transposons of the Tn916 family and for an unknown clindamycin resistance determinant. Transfer rates of up to 10−5 transconjugants per donor were obtained with a L. monocytogenes recipient and up to 10−7 with an Enterococcus faecalis recipient, respectively. Although the prevalence of acquired antibiotic resistance in Listeria isolates from this study was rather low, the transferability of these resistances enables further spread in the future. This endorses the importance of surveillance of L. monocytogenes and other Listeria spp. in terms of antibiotic susceptibility.